Production of Methyl Laurate from Coconut Cream through Fractionation of Methyl Ester - Sitompul, Johnner P.; Istyami, A.N.; Muhtadi, R.; Lee, H.W.; Rahman, H. (Journal of Engineering and Technological Sciences, 2015)
This paper concerns the production of methyl laurate from coconut cream through fractionation of methyl esters. Coconut oil was produced by wet processing of coconut cream. The esters were prepared by reacting coconut oil and methanol using homogeneous catalyst KOH in a batch reactor, followed by fractionation of fatty acid methyl esters (FAME) at various reduced pressures applying differential batch vacuum distillation. Experimental data were compared with simulation of a batch distillation employing the simple Raoultâs model and modified Raoultâs model of phase equilibria. Activity coefficients (Î³i) were determined by optimization to refine the models. The modified Raultâs model with activity coefficients gave better agreement with the experimental data, giving the value of Î³i between 0,56-0,73. For a given boiling temperature, lower operating pressure produced higher purity of C10 and C12 FAME for respective distillates.